1999
DOI: 10.1095/biolreprod60.5.1110
|View full text |Cite
|
Sign up to set email alerts
|

Growth Retardation of Inner Cell Mass Cells in Polyspermic Porcine Embryos Produced In Vitro1

Abstract: The in vitro viability of polyspermic pig eggs was investigated. Immature oocytes were matured and fertilized in vitro. Approximately 10 h after insemination, the eggs were centrifuged at 12 000 x g for 10 min and individually classified into two (2PN)- and poly-pronuclear (PPN, 3 or 4 pronuclei) eggs. The classified eggs were cultured in vitro or in vivo. Nuclei numbers of inner cell mass (ICM) and trophectoderm (TE) were compared between 2PN- and PPN-derived blastocysts. The frequency of development in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 28 publications
7
51
1
1
Order By: Relevance
“…This result was consistent with a recent publication (Gil et al 2004). It has also been demonstrated that polyspermic porcine IVM -IVF embryos containing multiple pronuclei can develop in vitro to the blastocyst stage at the same percentage as monospermic IVM-IVF embryos (Han et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with a recent publication (Gil et al 2004). It has also been demonstrated that polyspermic porcine IVM -IVF embryos containing multiple pronuclei can develop in vitro to the blastocyst stage at the same percentage as monospermic IVM-IVF embryos (Han et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…9,10 In our study, the blastocyst development efficiency of the 3PN group was 10.8%, which is accordance with our previous report. 11 The clinical treatment and culture conditions might have contributed to this difference.…”
Section: Discussionsupporting
confidence: 92%
“…9 In a porcine study, Han et al indicated that at least 40% of 3PN zygotes could develop to the blastocyst stage, but the cell number in the inner cell mass (ICM) was decreased when compared with diploid blastocysts. 10 Recently, Chen et al derived one triploid ES cell line and three diploid ES cell lines from 12 blastocysts that were developed from 130 3PN zygotes, suggesting that polyspermic embryos could serve as an alternative source for normal euploid human embryonic stem cell (hES cell) lines. 11 In 1989, Malter et al tried to reconstruct a diploid zygote using microsurgery; 1 blastocyst was obtained using microsurgery from seven tripronuclear human zygotes.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of PN4-PN5 zygotes obtained in vitro that we analysed in our experiments was lower compared with the percentage of PN produced in vitro by other authors, but this could be because of the IVF procedure utilized, where a high concentration of spermatozoa was used to fertilize within a short window of IVF in order to synchronize the beginning of the fertilization process. In contrast, the incidence of normospermic fertilization cannot be deduced from the percentage of IVM/IVF zygotes that reached the blastocyst stage in vitro, since clear evidence has demonstrated that, in the pig, a percentage of embryos reach this stage of development even following polyspermic fertilization (Han et al 1999, Kikuchi 2004.…”
Section: Discussionmentioning
confidence: 99%